Les Nouveaux Territoires de l’Art, entre îlot et essaim - Nicolas Aubouin; Emmanuel Coblence (Territoire en Mouvement)
Artistic approaches in brownfield sites or abandoned buildings, which fall under the term “New Territories of Art” (Nouveaux Territoires de l’Art), appear as new exploration fields for creation and management. In fact, these approaches renew the ways in which art projects are constructed, notably through the creation of multidisciplinary art communities and the involvement of stakeholders (population, socio-cultural associations, local authorities). In this process, the artist is in charge a central clearing role. However, this renewal, facilitated by the ergonomic design and location of the invested spaces, is also achieved through the introduction of more flexible management tools (collegiality, flexibility, informal selection) than those traditionally developed in cultural institutions. Through the case study of two artistic wastelands in France, Les Frigos and Culture Commune, we show that the development of these areas needs an interaction with their settlement territory, which can be achieved by many different paths, depending on the contexts and strategies of project leaders. We distinguish two models of development: the island (îlot) is based on a project management devoted to autonomy, while the swarm (essaim) develops through a co-construction with the territory. These two logics, although much different, both lead to challenge traditional public governance in the field of culture.